Implementation Challenges of Automated Construction Progress Monitoring under Industry 4.0 Framework Towards Sustainable Construction - Qureshi, A.H. (Institute of Electrical and Electronics Engineers Inc., 2021)
Industry 4.0 and progress monitoring via digital technologies for sustainable construction projects are greenfield areas among the research community. However, special consideration is required towards the effective implementation of the Industry 4.0 theme in automated construction progress monitoring processes as an emerging concept, as it leads to sustainable construction. This study intends to identify the macro-level and the micro-level implementation challenges towards sustainable automated progress monitoring processes under the Industry 4.0 framework. The Industry 4.0 operational framework was developed for automated construction progress monitoring to review the whole process, based on the collected literature. This study divides the automated progress monitoring process into three categories, and challenges were highlighted separately, based on the specific mode of operation. The study also highlights the Industry 4.0 challenges in the execution of automated construction progress monitoring and the remedial actions for procedural improvements. Â© 2021 IEEE.